Abundance and Diversity of Mushroom Coral of the Fungiidae in the Waters of Pasumpahan Island, West Sumatra - Pratama, Farrel; Thamrin, Thamrin; Nurrachmi, Irvina (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Mushroom coral (Fungiidae) is one of the families of hard corals (scleractinian) that live off the substrate (free-living), and most of the mushroom coral habitat is found on the reef slope, which has a substrate of broken coral. This study aimed to analyze the abundance and diversity and determine the differences in abundance of mushroom corals at different depths. This research was conducted in March 2024 in Pasumpahan Island, West Sumatra. This study used the survey method and belt transect method. The sampling location was divided into three stations consisting of 3 sampling points. Station I is located in the tourist area, Station II is in the dock area, and Station III is in the area facing the open sea. The results showed that the highest abundance based on depth was found at station III with a depth of 7 m, namely 4357.14 ind/Ha and the lowest abundance at station II with a depth of 5 m, namely 1285.71 ind/Ha. The t-test results obtained a significant value of less than 0.05, namely 0.048, which means that the abundance of mushroom corals at different depths is significantly different. The diversity index ranges from 1.930 to 2.013, which shows that the level of diversity of mushroom corals in the waters of Pasumpahan Island is classified as moderate